Are all of the services offered in the Urban Family physician program free? The perspective of administrators and executives - Mohammad Javad Kabir; Hassan Ashrafian Amiri; Seyed Mozafar Rabiee; Anahita Keshvarzi; Sohila Hoseini; Seiyed Davoud Nasrollahpour Shirvani (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: Patient involvement in paying the out-of-pocket medical expenses is common in most countries. According to the instructions of the Urban Family Physician Program in Iran (Version 02), all care services should be provided free of charge. This study aimed to investigate the viewpoints of administrators and executives in Fars and Mazandaran provinces regarding the free provision of services. Methods: This cross-sectional study was conducted in winter 2016. The study population included administrators and experts monitoring the Urban Family Physician Program, as well as representatives of Family Physicians who were selected by the census. The data were collected using a researcher-made questionnaire containing two parts with 20 items. In addition, The reliability and validity of this questionnaire were confirmed using alpha Cronbach at 0.87%. The data were collected from 29 expert panels in cities of Fars and Mazandaran. The obtained data were analyzed in SPSS software (version. 23). P-value less than 0.05 was considered statistically significant. Results: Out of 635 participants, 49 cases (7.7%) agreed that all services provided by family physicians and health care providers should be free. According to the results, free of charge services include care for chronic diseases (63.7%), basic visits and periodic examinations (48.1%), injections (40.4%), serum therapy (36.6%), bandaging (35.2%), therapeutic visits (22.8%), prescriptions of family physicians (22.6%), laboratory services (17.3%), and radiography and ultrasound services (15.7%). Conclusion: This study showed that the majority of people disagreed with free of charge services provided by urban family physicians. Therefore, it is suggested to revise franchise systems regarding the provision of some services.